2023
DOI: 10.1038/s41598-023-34319-0
|View full text |Cite
|
Sign up to set email alerts
|

Influence of face masks on the subjective impairment at different physical workloads

Abstract: To quantify the subjective and cognitive impairment caused by wearing face masks at work, 20 men and 20 women (median age 47 years, range 19–65) were tested under different ergometer workloads while wearing surgical mask, community mask, FFP2 respirator or no mask in a randomized and partially double-blinded design. Masks were worn also at the workplace for four hours. Subjective impairment was recorded by questionnaires. Cognitive performance was tested before and after the workplace examination. Subjective f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…In the first section, participants' socio-demographic data, including gender, age, body mass (kg), height (m) and professional role (doctor, nurse, nursing aide), were collected; Section 2: Perceived workload and issues in FFP2 use. In the second section, based on Van Kampen et al [44], Matusiak et al [45] and Peres et al [21], participants were asked to rate on a 3-point scale (1 = mild, 2 = moderate, 3 = high) the perceived level of physical workload required for their job and the number of hours of FFP2 use per day (open question). Using a short open-ended question [21], participants were then asked to describe the positive and negative aspects when using FFP2 masks.…”
Section: Instruments and Proceduresmentioning
confidence: 99%
“…In the first section, participants' socio-demographic data, including gender, age, body mass (kg), height (m) and professional role (doctor, nurse, nursing aide), were collected; Section 2: Perceived workload and issues in FFP2 use. In the second section, based on Van Kampen et al [44], Matusiak et al [45] and Peres et al [21], participants were asked to rate on a 3-point scale (1 = mild, 2 = moderate, 3 = high) the perceived level of physical workload required for their job and the number of hours of FFP2 use per day (open question). Using a short open-ended question [21], participants were then asked to describe the positive and negative aspects when using FFP2 masks.…”
Section: Instruments and Proceduresmentioning
confidence: 99%
“…Although the impact on the user’s health is minimal, some studies have shown possible side effects related to prolonged use of masks such as headache, irritation and dry eyes and skin conditions (appearance or worsening of acne and other facial dermatoses, including rosacea, dermatitis seborrheic, and irritant contact dermatitis) [ 27 ]. An impact on the subjective appreciation of effort when performing physical activities has also been described [ 28 ].…”
Section: Disadvantages Of Maintaining the Obligatory Nature Of Its Usementioning
confidence: 99%
“…Exercise and being overweight could further increase the facial temperature, perceived breathing effort, and thermal discomfort [37][38][39][40][41]. Wearing N95 and surgical masks was shown to increase the heart rate and subjective sensations of discomfort in healthy volunteers but did not significantly impact thermal stress [42][43][44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%